2020
DOI: 10.1186/s12951-020-00600-x
|View full text |Cite|
|
Sign up to set email alerts
|

Astaxanthin-loaded polymer-lipid hybrid nanoparticles (ATX-LPN): assessment of potential otoprotective effects

Abstract: Background: Ototoxicity is one of the major side effects of platinum-based chemotherapy, especially cisplatin therapy. To date, no FDA approved agents to alleviate or prevent this ototoxicity are available. However, ototoxicity is generally believed to be produced by excessive generation of reactive oxygen species (ROS) in the inner ear, thus leading to the development of various antioxidants, which act as otoprotective agents. Astaxanthin (ATX) is an interesting candidate in the development of new therapies f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Several studies have reported that mechanotransducer (MET) channels mediate the entry of cisplatin into cochlear hair cells, but it remains unclear whether MET channels are blocked during that process. 30,46,53 A study using larval zebrafish confirmed that cisplatin-induced damage to the hair cells relies on functional MET channels. 19 Furthermore, the effect of platinum (II) complexes on adult zebrafish auditory system suggested that cisplatin, and to a limited extent phenanthriplatin, can induce hair cells loss in particular regions of the saccule but not the utricle, 56 suggesting either various regional susceptibility to cisplatin or its distinct diffusion or transport pattern.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have reported that mechanotransducer (MET) channels mediate the entry of cisplatin into cochlear hair cells, but it remains unclear whether MET channels are blocked during that process. 30,46,53 A study using larval zebrafish confirmed that cisplatin-induced damage to the hair cells relies on functional MET channels. 19 Furthermore, the effect of platinum (II) complexes on adult zebrafish auditory system suggested that cisplatin, and to a limited extent phenanthriplatin, can induce hair cells loss in particular regions of the saccule but not the utricle, 56 suggesting either various regional susceptibility to cisplatin or its distinct diffusion or transport pattern.…”
Section: Discussionmentioning
confidence: 97%
“…Overproduction of ROS can activate the signal transducer and activator of transcription 1 (STAT1), inducing the inflammation. 46 Previous studies have shown that ROS might induce autophagy, which, depending on the stimulation context, can promote either cell survival or lead to cell death. 54,55 The critical step responsible for the ototoxic properties of cisplatin is its transport inside the sensory cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that AST protected against cisplatin-induced hearing loss (CIHL) at high frequencies in rats and neomycin-induced lateral-line HC death in zebra fish 19 , 20 . It is suggested that the antioxidant activity of AST is associated with several potential mechanisms, including the activation of MAPK, nuclear factor erythroid 2-related factor 2 (NRF2)/antioxidant response element (ARE), and PI3K/AKT pathways 21 , 22 , 23 .
Figure 1 Molecular docking and dynamic analysis of astaxanthine and KEAP1.
…”
Section: Introductionmentioning
confidence: 99%
“…As per Jiayi Gu et al studies, astaxanthin encapsulated lipid-polymer hybrid nanoparticles have a greater effect against cisplatin-induced toxicity [16]. As per Salam Massadeh et al research, anastrozole was encapsulated by a polyethylene glycolated (PEGylated) polymer-lipid hybrid nanoparticulate device using a direct emulsification solvent evaporation process [17].…”
Section: Introductionmentioning
confidence: 99%